Index of the Cycle of Money - The case of Georgia - Constantinos Challoumis (ეკონომიკური პროფილი)
This paper aims to establish how the theoretical background of the cycle of money applies to a real-world scenario, specifically focusing on the economic system of Georgia. The cycle of money index measures how an economic system can counteract a monetary crisis and assesses the structural robustness of a country's economy. The index calculations for Georgia are compared to the global average, providing insight into the country's economic health and its capacity to withstand economic crises. The conclusions indicate that Georgia's index is under but dynamically increased achieving to meet the global average, suggesting that its economy is relatively strong and capable of facing economic challenges. The methodology applied in this study adheres to established theories, utilizing mathematical, statistical, and econometric techniques to arrive at its conclusions. This research is significant as it highlights the resilience of Georgia's economy in the face of potential crises. The findings align with prior studies on the cycle of money index in other countries, such as Latvia, Bulgaria, Serbia, Thailand, and Greece. According to this theory, companies with substantial capital should focus their investments on manufacturing and high-technology sectors, benefiting from reduced taxes to ensure better money distribution across the economy. Smaller companies would then address other economic sectors, promoting overall economic balance. This study is part of a broader project that examines the cycle of money index across multiple countries, marking the first time such an analysis has been conducted for Georgia. The period analyzed for this study spans the global recession from 2012 to 2017.